A Fast Finite-Difference Time Domain Simulation Method for the Source-Stirring Reverberation Chamber - Wenxing Li; Chongyi Yue; Atef Elsherbeni (International Journal of Antennas and Propagation)
Numerical analysis methods are often employed to improve the efficiency of the design and application of the source-stirring reverberation chamber. However, the state of equilibrium of the field inside the chamber is hard to reach. In this paper, we present a fast simulation method, which is able to significantly decrease the simulation time of the source-stirring reverberation chamber. The mathematical model of this method is given in detail and home-made FDTD code is employed to conduct the simulations and optimizations as well. The results show that the implementation of the method can give us the accurate frequency response of the source-stirring chamber and make the simulation of source-stirring chamber more efficient.